2020
DOI: 10.1039/d0gc01983f
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorescent bio-based resin for digital light processing (DLP) 3D-printing

Abstract: This work presents a novel bio-based resin for DLP 3D printing using a photocurable polyester obtained from renewable resources. The ink is formulated with phosphorescent Ir-complexes and printed for both rigid and flexible structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…The G and E monomers were mixed, in differen molar ratios, to test the reactivity and the performance; a third component, a cross-linke was then introduced to achieve the high photo-reactivity necessary for the SLA proces Two cross-linkers were selected, that is, a widely used commercial one (trimethylolpro pane-trimethacrylate, T in Figure 10) and a natural synthesized one (vanillin-dimethacry late, V in Figure 10). Maturi et al [65] developed a new resin for digital light processing (DLP)-based 3D printing. The important feature of this resin was the extremely high bio-based content of 96.5%.…”
Section: The Photopolymerization Of Lignin and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The G and E monomers were mixed, in differen molar ratios, to test the reactivity and the performance; a third component, a cross-linke was then introduced to achieve the high photo-reactivity necessary for the SLA proces Two cross-linkers were selected, that is, a widely used commercial one (trimethylolpro pane-trimethacrylate, T in Figure 10) and a natural synthesized one (vanillin-dimethacry late, V in Figure 10). Maturi et al [65] developed a new resin for digital light processing (DLP)-based 3D printing. The important feature of this resin was the extremely high bio-based content of 96.5%.…”
Section: The Photopolymerization Of Lignin and Its Derivativesmentioning
confidence: 99%
“…Maturi et al [ 65 ] developed a new resin for digital light processing (DLP)-based 3D printing. The important feature of this resin was the extremely high bio-based content of 96.5%.…”
Section: Uv-curable Monomers From the Pulp And Paper Industrymentioning
confidence: 99%
“…Despite the lower intrinsic reactivity of its carbon–carbon double bond toward UV-induced radical polymerization, itaconic acid has been successfully used as a UV-curable building block to produce numerous crosslinkable resins for coating, printing ink, or additive manufacturing applications. However, in the case of itaconic acid, the synthesis of smaller compounds with low viscosity and high reactivity is much more challenging than the design of UV-curable polymeric resins. Indeed, when used in a linear or hyperbranched polymer, it is possible to increase the reactivity of the material by increasing the double bond density and the accessibility of these double bonds or change the components.…”
Section: Introductionmentioning
confidence: 99%
“…164 This criterion limits the materials that can be used: high molecular weight photopolymers are often too viscous to be used on their own, requiring the addition of solvents or reactive diluents (low viscosity monomers) to reduce the viscosity of the photoresin. 165,166 For example, Strohmeier et al reported the use of divinyl ethers as reactive diluents to reduce the viscosity of methacrylated liquid isoprene rubber from 79 Pa s to <6 Pa s, allowing it to be used with DLP printing. 167 Photosensitive slurries used in ceramic VP need to carefully manage their solid loadings such that they are low enough for their viscosities to be manageable but still sufficiently high that the final ceramic part has the desired properties.…”
Section: Viscositymentioning
confidence: 99%